Enhanced spatial modulation with generalized antenna selection in MISO channels. Issue 16 (4th June 2021) - Qing, Hua; Yu, Hua; Liu, Yun; Wen, Miaowen
Abstract: Here, an enhanced spatial modulation with generalized antenna selection (ESM‐GAS) for multiple‐input single‐output systems is proposed. Unlike the conventional SM systems, in ESM‐GAS, the number of active antennas is not fixed, but varies from only one to all. In ESM‐GAS, a concept called equivalent antennas is introduced to describe the status of the antennas. Out of all the available equivalent antennas, a subset is selected as the candidate antennas for SM, in which additional information bits are used to determine the indices of the activated equivalent antennas. Two criteria are used to select the candidate equivalent antennas. One is ESM‐GAS, where a part of candidate equivalent antennas with larger channel power gains are selected with low computational complexity. To further improve the bit error ratio (BER) performance of ESM‐GAS, the other one is a combination scheme of Euclidean distance antenna selection (EDAS) and ESM‐GAS (ESM‐GAS‐EDAS). Simulation results show that ESM‐GAS has better BER performance than conventional SM, and ESM‐GAS‐EDAS outperforms conventional SM, EDAS‐based SM, and ESM‐GAS, which verifies the effectiveness of the proposed schemes.